2009
DOI: 10.1027/0227-5910.30.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate Self-Harm in the Emergency Department

Abstract: Patients who left the ED without psychosocial assessment are at increased risk for repetition of DSH as well as suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 15 publications
4
12
0
Order By: Relevance
“…This is similar to findings from other recent Sri Lankan and Asian studies [13-16,39] and is in accordance with internationally established patterns of higher rates of attempted suicide and self-harm among females [6,17,40]. This finding is unlikely to be a reflection of the distribution of males and females in the population, given that the 2001 population census for Sri Lanka reports a male:female gender ratio of 0.99:1.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is similar to findings from other recent Sri Lankan and Asian studies [13-16,39] and is in accordance with internationally established patterns of higher rates of attempted suicide and self-harm among females [6,17,40]. This finding is unlikely to be a reflection of the distribution of males and females in the population, given that the 2001 population census for Sri Lanka reports a male:female gender ratio of 0.99:1.…”
Section: Discussionsupporting
confidence: 93%
“…Similar patterns of change have been reported in other countries in the Asian regions such as Pakistan and Vietnam [15,16]. With increasing urbanization, patterns of non-fatal self-poisoning in Sri Lanka and other South Asian countries may be changing to resemble that of developed countries, accompanied by an increasing proportion of attempted suicides among females [13-16]. …”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…This appears to signify a trend that has been emerging in the last decade, of an increasing ratio of non-fatal self-poisoning among females compared to males in urban areas, paralleled by an increase of pharmaceutical drug overdoses rather than pesticide self-poisoning in these areas. Other developing countries too have shown similar gender differences of non-fatal self-poisoning in rural compared to urban areas [45,53]. For example, a study undertaken in Hanoi, Vietnam [45] reported a higher female-to-male ratio of non-fatal self-poisoning in urban areas where medicinal overdose is more common, compared to rural areas where pesticides ingestion is more common.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, intentional poisonings are a medicolegal cases, and socially unacceptable in Pakistan. As such, individuals tend to avoid presenting to a hospital for fear of reporting and the social stigma [ 20 ].…”
Section: Discussionmentioning
confidence: 99%